Manajemen Pembiayaan Pendidikan yang Efektif di Madrasah Tsanawiyah Swasta - Amaliyah, Kholishotul; Giu, Isra Yanuar (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
Education financing is crucial for supporting operational needs, staff salaries, employee welfare, improving the teaching and learning process, maintaining and acquiring facilities and infrastructure, enhancing student guidance, improving teacher professional development, educational administration, and supervision. The quality of the teaching and learning process can be enhanced when the set objectives meet the necessary requirements. However, the education sector in Indonesia faces various serious issues, including inadequate budget allocation from the government. This research aims to describe the practices and identify effective education financing management to enhance access and the quality of education in MTs Sains Qurani Azzakiyyah. The research employs a descriptive method with a qualitative approach, utilizing interviews, observations, documentation, and literature review for data collection. The results indicate that effective education financing management involves optimizing the use of available funds, allocating budgets efficiently, and distributing resources to support an effective learning process. Key findings include specific strategies implemented at MTs Sains Qurani Azzakiyyah that led to significant improvements in educational quality and accessibility. Optimal management of educational costs is essential for achieving high standards in school quality.